The effect of tanshinones on cognitive impairments in animal models of Alzheimer’s disease: a systematic review and meta-analysis - Wang, Shuwei; Yang, Jinsha; Zheng, Wenbin; Zhang, Serena; Zhong, Dayong (Frontiers in Pharmacology, 2025)
BackgroundAlzheimer’s disease (AD) is an age-related neurological illness that poses a significant hazard to human health. A fat-soluble compound called tanshinones was isolated from Danshen, a traditional Chinese herb. Recent years have seen reports of clinical trials examining the effects of tanshinones on cognitive impairment among individuals with AD, as well as the publication of pertinent basic research. Tanshinones are not yet commonly utilized in the therapeutic treatment of AD, and the effectiveness of tanshinones as a treatment program for AD is not yet adequately supported by evidence. To assess the impact of tanshinones on cognitive impairment in experimental rodent models of AD, we carried out a systematic review in this work.MethodAll relevant studies on the usage of tanshinones in AD model animals published in PubMed, Cochrane Library, Web of Science, EMBASE, Chinese Biomedicine Database, and China National Knowledge Infrastructure before 8 September 2024, were systematically retrieved. To assess the methodological quality, the CAMARADES checklist was used. Meta-analysis was calculated and graphed in the Stata 14.0 software. For each outcome in every study, the standard mean difference (SMD) and the 95% confidence interval (CI) of each effect size were calculated.ResultsFourteen studies were included in this study. Compared with the AD model group without tanshinones intervention, tanshinones significantly reduced the number of escape latency [SMD = −2.082, 95% CI = (−2.481, −1.683), p < 0.001]. Tanshinones also increased the times of platform crossing [SMD = 1.464, 95% CI = (1.183, 1.744), p < 0.001] and time in target quadrants [SMD = 2.703, 95% CI = (2.132, 3.275), p < 0.001].ConclusionTanshinones are thought to have positive effects on cognitive impairment in rodent models of AD, according to the findings of this study. However, the level of quality of the included research may have an impact on the accuracy of positive outcomes. Thus, more high-quality randomized controlled animal studies are required to guide future scientific and clinical research.Systematic Review Registrationidentifier CRD42024557980